The Experimental Test of Radial PE-Reinforced Polymer Pipe Under Short-Time Hydraulic Pressure - Krisnawan, Bagus; Arifi, Eva; Setyowulan, Desy (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
The resistance of thermoset polymer pipes to compressive forces is a concern in the reliability of piping infrastructure. To maintain the reliability of these piping systems, it is imperative to understand and improve the resistance of pipes. The use of polyethylene (PE) rope as Reinforce Polymer Pipe (RPP) composite material was tested with Short-Time Hydraulic Pressure to determine the stress-strain distribution as well as the durability of its mechanical properties. This study used 4mm diameter polyethylene rope arranged radially coiled inside a 40cm diameter polymer pipe with a thickness of 1cm using a mixture of Unsaturated Polyester Resin (UPR), fly ash, sand, catalys and cobalt. The test results show that the composite material has strong mechanical properties and is resistant to hydraulic compressive forces with an average deformation of 8.2 mm with an average maximum load of 33.57kN with the polymer experiencing cracks and damage but the polyethylene rope remains in good condition and has good ductile or elastic properties against compression without significant damage. The highest positive mean strain value of 0.4. The graph displays strain values that are continuously positive up to 50-100 seconds and then drop to negative values quickly indicating that the polymer pipe provides good resistance at the beginning of 50-100 seconds and then experiences damage but the pipe can still return to its original shape with damage to the polymer having an average maximum stress value of 5.23 Mpa with an average duration of 266 seconds while the lowest stress value is 3.34 Mpa.